GERAKAN SHALAT SEBAGAI EPISTEMOLOGI RUHANI PERSPEKTIF NUR MUHAMMAD - Moch Aziz Tofan,; Muhammad Akmansyah,; M. Afif Anshari, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
This article presents an in-depth study of the movements of Shalat (Islamic prayer) as a form of spiritual epistemology, particularly from the perspective of the concept of Nur Muhammad. This research adopts a qualitative approach with a descriptive-analytical method, designed to carefully explore and interpret the symbolic meanings contained within each posture and transitional movement of Shalat. Its primary objective is to understand how this series of physical movements functions as an effective means of acquiring profound and authentic spiritual knowledge. The study's findings reveal significant insights: each movement in Shalat represents systematic and essential stages in the human spiritual journey towards closeness with God. This spiritual journey is fundamentally rooted in the concept of Nur Muhammad, understood as the primordial light of creation, the first entity created by Allah, and the origin of all manifestations in the universe. Thus, Shalat is not merely a ritual, but a symbolic "mi'raj" (ascension) that allows the worshipper to align themselves with this original light. This research is expected to make a substantial contribution to deepening the understanding of the esoteric and philosophical dimensions of Shalat, moving beyond its literal interpretations. Furthermore, this study also aims to enrich the treasury of Islamic epistemology by offering a new perspective on how the practice of worship can become a path towards the acquisition of intuitive and direct Divine knowledge.